Negative electrode active material for secondary battery, and secondary battery

By using silicon-containing particles with a pore size distribution ranging from 2nm to 100nm and an average pore size of more than 50nm and less than 100nm, the problem of reduced capacity retention caused by expansion and contraction during the charging and discharging process of silicon anode materials is solved, and better cycle characteristics and capacity retention are achieved.

CN121002673APending Publication Date: 2025-11-21PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202480028041.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-04-27
Filing Date
2024-04-17
Publication Date
2025-11-21

AI Technical Summary

Technical Problem

Silicon-containing anode materials undergo side reactions during charging and discharging due to expansion and contraction, which affects capacity retention.

Method used

The composite particles containing silicon particles are used, with a fine pore size distribution in the range of 2nm to 100nm and an average fine pore size of more than 50nm and less than 100nm. The particles contain an ion-conducting phase and a silicon phase dispersed therein. The expansion and contraction of silicon particles are suppressed by controlling the fine pore size distribution.

Benefits of technology

It effectively suppresses the expansion and contraction of the negative electrode active material, and improves the capacity retention rate and cycle characteristics during charge and discharge cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121002673A_ABST
    Figure CN121002673A_ABST
Patent Text Reader

Abstract

A negative electrode active material for a secondary battery, the negative electrode active material containing silicon-containing particles, the silicon-containing particles containing an ion-conducting phase and a silicon phase dispersed in the ion-conducting phase, the silicon-containing particles having a pore diameter distribution in which the average pore diameter on a volume basis within the pore diameter range of 2-100 nm is 50-100 nm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to negative electrode active materials for secondary batteries and secondary batteries having negative electrode active materials for secondary batteries. Background Technology

[0002] In the negative electrode of secondary batteries, such as lithium-ion batteries, a negative electrode active material capable of absorbing and releasing lithium ions is used. Graphite is commonly used as such a negative electrode active material. In recent years, composite materials containing silicon, which has a higher capacity density than graphite, have been studied regarding negative electrode active materials (e.g., Patent Document 1).

[0003] Existing technical documents

[0004] Patent documents

[0005] Patent Document 1: International Publication No. 2020 / 110917 Summary of the Invention

[0006] The problem that the invention aims to solve

[0007] Materials containing silicon show promise as high-capacity anode materials for secondary batteries. However, silicon-containing materials exhibit significant expansion and contraction during charging and discharging, which can easily induce side reactions and reduce capacity retention during charge-discharge cycles.

[0008] Methods for solving problems

[0009] In view of the above, one aspect of this application relates to a negative electrode active material for a secondary battery, which comprises silicon-containing particles, wherein the silicon-containing particles comprise an ion-conducting phase and a silicon phase dispersed within the ion-conducting phase, and in the micropore size distribution of the silicon-containing particles, the average micropore size on a volume basis in the micropore size range of 2 nm to 100 nm is 50 nm or more and 100 nm or less.

[0010] Another aspect of this application relates to a secondary battery having a positive electrode, a negative electrode, and an electrolyte, wherein the negative electrode comprises the aforementioned negative electrode active material for a secondary battery.

[0011] Invention Effects

[0012] According to this application, the expansion and contraction of the negative electrode active material in a secondary battery during charging and discharging is suppressed.

[0013] While novel features of the invention are described in the appended technical solutions, both the structure and content of the invention, along with its other objects and features, can be better understood from the following detailed description taken in conjunction with the accompanying drawings. Attached Figure Description

[0014] Figure 1This is a cross-sectional view schematically illustrating an example of a negative electrode active material (silicon-containing material) according to one embodiment of this application.

[0015] Figure 2 This is a schematic perspective view of a secondary battery according to one embodiment of this application, after a portion has been removed. Detailed Implementation

[0016] The following description illustrates embodiments of this application using examples, but this application is not limited to the examples described below. In the following description, specific numerical values ​​and materials are sometimes illustrated, but other numerical values ​​and materials can be applied as long as the desired effect of this application is achieved. In this specification, the phrase "numerical value A to numerical value B" includes both numerical value A and numerical value B, and can be replaced with "numerical value A or higher and numerical value B or lower." In the following description, when lower and upper limits are illustrated for specific physical properties, conditions, etc., any illustrated lower limit can be arbitrarily combined with any illustrated upper limit, as long as the lower limit is not higher than the upper limit. When multiple materials are illustrated, one can be selected for use alone, or two or more can be used in combination.

[0017] Furthermore, this application includes a combination of matters described in any two or more technical solutions selected from the plurality of technical solutions described in the appended claims. That is, as long as no technical contradiction arises, a combination of matters described in any two or more technical solutions selected from the plurality of technical solutions described in the appended claims is permissible.

[0018] (Negative electrode active material for secondary batteries)

[0019] One embodiment of this application discloses a negative electrode active material for a secondary battery that comprises silicon-containing particles. The silicon-containing particles comprise an ion-conducting phase and a silicon phase dispersed within the ion-conducting phase. Hereinafter, the silicon-containing particles are also referred to as "composite particles".

[0020] The ion-conducting phase may, for example, comprise at least one selected from silicate phases and silicon oxide phases. Hereinafter, at least one of the silicate phase and silicon oxide phase is also referred to as a "silicon compound phase." Silicon compound phases can form amorphous phases. Composite particles in which a silicon phase is dispersed within a silicate phase are also referred to as "composite particles containing a silicate phase." Composite particles in which a silicate phase, where the silicate phase is lithium silicate, are also referred to as "composite particles containing a lithium silicate phase." Composite particles in which a silicon phase is dispersed within a silicon oxide phase are also referred to as "composite particles containing a silicon oxide phase."

[0021] In the fine pore size distribution of silicon particles, the average pore size on a volume basis within the range of 2 nm to 100 nm is greater than 50 nm and less than 100 nm. Under this condition, the expansion and contraction of silicon particles during charging and discharging are suppressed, and the cycle characteristics are improved.

[0022] In the micropore size distribution of silicon particles, the range of micropore size from 2 nm to 100 nm is divided into two parts. The range with micropore size greater than 2 nm and less than X is designated as region 1, and the range with micropore size greater than X and less than 100 nm is designated as region 2. Hereinafter, the average micropore size based on volume is the value X of the micropore size when the cumulative micropore volume in region 1 is equal to the cumulative micropore volume in region 2. That is, the average micropore size is the median particle size of the volume reference within the range of micropore size from 2 nm to 100 nm, hereinafter also referred to as "average micropore size D50".

[0023] Silicon-containing particles with an average pore size D50 of 50 nm or more possess a well-developed macropore structure with pore sizes of 20 nm or more. During charge and discharge, the silicon phase expands or contracts. The expanded silicon phase fills a portion of the voids, thereby suppressing overall volume changes in the silicon-containing particles. This expansion and contraction of the silicon phase reduces the stress applied to the ion-conducting phase, thus suppressing the breakage of the ion-conducting phase and inhibiting side reactions with the electrolyte that originate from this breakage. Therefore, the decrease in capacity retention during charge-discharge cycles can be suppressed.

[0024] In particular, silicon-containing particles with an average pore size D50 of 50 nm or more have a large number of pores with a pore size similar to that of the silicon phase. Therefore, as the silicon phase expands, the silicon phase easily fills these pores, and the stress associated with the expansion is difficult to transfer to the ion-conducting phase. Thus, it is believed that suppressing the expansion and contraction of silicon-containing particles during charging and discharging can effectively suppress the decrease in capacity retention.

[0025] From the perspective of improving cycle performance, the average pore size D50 of silicon particles should be above 50 nm. The average pore size D50 can be above 55 nm and below 100 nm, above 60 nm and below 100 nm, above 65 nm and below 100 nm, or above 60 nm and below 90 nm.

[0026] The average pore size D50 can be determined by measuring the pore size distribution of silicon-containing particles using pore size analysis methods such as the BET method.

[0027] Regarding the pore size distribution, a sample containing silicon particles of 0.20 g to 0.25 g was placed in a measurement cell made of a glass tube used for specific surface area measurement. The sample was dried and degassed within the measurement cell before measurement. The drying and degasing process was carried out at a pressure of 6.67 Pa and a temperature of 250 °C ± 5 °C for at least 1 hour. The negative electrode could be removed by disassembling the secondary battery, washed with a solvent such as dimethyl carbonate, and the negative electrode binder layer was extracted from the dried negative electrode. The silicon particles were then separated and used as the sample. The mass of the sample in the measurement cell was then measured to the order of 0.1 mg. The nitrogen adsorption of the sample at -196 °C was then measured using a specific surface area measurement device. For example, the automatic specific surface area / pore size distribution measuring device "TriStar II 3020" manufactured by Shimadzu Corporation was used. Based on the adsorption measurement results, the volume-based pore size distribution was determined using the BET multi-point method.

[0028] In the logarithmic differential fine pore volume distribution, the total fine pore volume V1 within the range of 2nm to 100nm is calculated by accumulating (integrating) the fine pore volume over this range. Then, the logarithmic differential fine pore volume distribution is accumulated from the 100nm fine pore diameter towards the smaller fine pore diameter, and the fine pore diameter X at which the total logarithmic differential fine pore volume equals half of V1 is calculated. This is taken as the average fine pore diameter D50.

[0029] The average pore size D50 can be controlled, for example, by the conditions of the ball milling process when pulverizing and micronizing the mixture of silicate and raw silicon using a ball mill or similar equipment in the manufacturing process described later, and / or the heat treatment conditions when heat-treating the micronized mixture. For example, the longer the heat treatment time, the easier it is for the silicate phase to flow in a way that fills the pores, thus reducing the porosity. In this case, the silicate phase flows in a way that preferentially fills the larger pores, thus reducing the average pore size D50. In addition, the longer the ball milling time, the finer the raw material particles, and the more sintering points are formed in the subsequent heat treatment process, thus reducing the average pore size D50.

[0030] (Composite particles)

[0031] The composite particles have a structure in which a silicon phase is dispersed within an ion-conducting phase (matrix). The stress caused by the expansion and contraction of the silicon phase during charge and discharge is mitigated by the ion-conducting phase, suppressing cracking and breakage of the composite particles. Therefore, both the high capacity and improved cycle performance resulting from the silicon content can be achieved. Furthermore, by maintaining an average pore size of 50 nm or more and 100 nm or less, the expansion and contraction of the composite particles during charge and discharge are suppressed, significantly improving cycle performance. The ion-conducting phase can consist of a single phase or multiple phases.

[0032] The silica phase is composed of compounds of Si and O. The main component of the silica phase (e.g., 95–100% by mass) can be silicon dioxide. The composite particles can be composite particles containing the silica phase. For example, composite particles containing the silica phase consist of SiO₂. x The expression is given by the formula (0.5≤x<1.6).

[0033] The silicate phase is composed of compounds containing a metallic element, silicon (Si), and oxygen (O). Examples of metallic elements include alkali metals such as lithium and Group 2 elements of the long-period periodic table. The silicate phase preferably contains at least lithium silicate. In this case, lithium ions readily enter and exit the silicate phase. The lithium silicate phase has a smaller irreversible capacity compared to the silicon oxide phase. The composite particles can be composite particles containing the silicate phase. The ion-conducting phase may contain, for example, a silicate phase as the main component, or a small amount of silicon oxide. Here, "main component" refers to a component that accounts for 50% or more by mass of the total mass of the silicon compound phase, or possibly 70% or more by mass. The silicate phase (lithium silicate phase) may contain at least one selected from Li₂Si₂O₅, Li₂SiO₃, and Li₄SiO₄.

[0034] The atomic ratio of O to Si in lithium silicate is, for example, greater than 2 and less than 4. When the O / Si ratio is greater than 2 and less than 4 (where z in the formula described later is 0 < z < 2), it is advantageous in terms of the stability of the silicate phase and lithium-ion conductivity. Preferably, the O / Si ratio is greater than 2 and less than 3. The atomic ratio of Li to Si in lithium silicate is, for example, greater than 0 and less than 4.

[0035] The composition of lithium silicate can be expressed by the formula: Li 2z SiO 2+z (0 < z < 2) indicates this. From the viewpoints of stability, ease of manufacture, and lithium-ion conductivity, z preferably satisfies the relationship 0 < z ≤ 1, and more preferably z = 1 / 2. For example, lithium silicate can be represented by Li₂SiO₃ when z = 1, and by Li₂Si₂O₅ when z = 1 / 2. Lithium silicate preferably contains Li₂Si₂O₅ as a main component, and Li₂Si₂O₅ is preferably the main component of the silicate phase as a whole. Here, "main component" refers to a component that accounts for 50% or more by mass of the total lithium silicate or silicate phase, and may also account for 70% or more by mass.

[0036] In addition to Li, Si, and O, silicate phases can also contain other elements M. By including other elements in the silicate phase, the chemical stability and lithium-ion conductivity of the silicate phase are improved, or side reactions caused by the contact between the silicate phase and non-aqueous electrolytes are suppressed.

[0037] The silicate phase may contain at least one element selected from alkali metals (excluding lithium) and group II elements as an element M other than Li, Si and O.

[0038] By including alkali metal elements other than Li in the silicate phase, crystallization becomes difficult, resulting in low viscosity and high fluidity in the softened state. Therefore, during heat treatment, it easily fills the gaps between silicon particles, readily generating dense composite particles. From a cost-effectiveness perspective, Na and / or K are preferred alkali metal elements.

[0039] Furthermore, while silicate phases are typically alkaline, Group II elements have the effect of inhibiting the dissolution of alkali metals from the silicate phase. Therefore, if the silicate phase contains Group II elements, the viscosity of the slurry containing the negative electrode active material is easily stabilized. Consequently, the necessity for treatment of the alkaline components (e.g., acid treatment) to neutralize the composite particles is reduced. The Group II elements can be either Ca or Mg. Ca is preferred in terms of its ability to improve the Vickers hardness of the silicate phase and further enhance cycling characteristics.

[0040] The silicate phase may also include at least one element M selected from boron (B), aluminum (Al), zirconium (Zr), niobium (Nb), tantalum (Ta), vanadium (V), lanthanum (La), yttrium (Y), titanium (Ti), phosphorus (P), bismuth (Bi), zinc (Zn), tin (Sn), lead (Pb), antimony (Sb), cobalt (Co), erbium (Er), fluorine (F), and tungsten (W). From the viewpoint of resistance to non-aqueous electrolytes and structural stability of the silicate phase, element M preferably includes at least one element selected from Zr, Ti, P, Al, and B.

[0041] The silicate phase may also contain rare earth elements as element M. Including rare earth elements in the silicate phase can improve the initial charge / discharge efficiency during charge / discharge cycles. The rare earth element can be any of scandium (Sc), yttrium (Y), and lanthanides. It should be noted that lanthanum (La), yttrium (Y), and erbium (Er) are rare earth elements. As a rare earth element, the silicate phase may contain at least one element selected from cerium (Ce), praseodymium (Pr), and neodymium (Nd). From the viewpoint of improving lithium-ion conductivity, La is more preferably included as a rare earth element. The proportion of La in the total rare earth element composition is preferably 90 atomic% or more and 100 atomic% or less.

[0042] Elements M, other than alkali metals and Group II elements, such as B, have low melting points, which is beneficial for improving fluidity during sintering. Al, Zr, and La can increase hardness while maintaining ionic conductivity. In addition, Zr, Ti, P, Al, and B have the effect of improving resistance to non-aqueous electrolytes and structural stability of silicate phases.

[0043] The silicate phase may also contain trace amounts of elements such as iron (Fe), chromium (Cr), nickel (Ni), manganese (Mn), copper (Cu), and molybdenum (Mo).

[0044] Element M can form compounds. Depending on the type of element M, these compounds can be, for example, silicates or oxides of element M. In the silicate phase, the content of element M relative to the total amount of elements other than oxygen is, for example, 1 mol% or more and 40 mol% or less.

[0045] The average particle size of the fine silicon phase dispersed within the ion-conducting phase (before the first charge) can be less than 500 nm, greater than 200 nm, or less than 50 nm. By making the silicon phase so moderately fine, the volume change during charge and discharge is reduced, and structural stability is improved. Furthermore, by homogenizing the expansion and contraction of the silicon phase, particle breakage is suppressed, thereby improving cycle characteristics. The average particle size of the silicon phase is determined by observing the cross-section of the composite particles using SEM or TEM. Specifically, it is calculated by averaging the maximum diameters of any 100 silicon phases.

[0046] The silicon phase dispersed within the ion-conducting phase is a particle-like phase of elemental silicon (Si), composed of single or multiple crystallites. From the viewpoint of minimizing volume changes caused by the expansion and contraction of the silicon phase (silicon particles) during charging and discharging, and easily improving cycle characteristics, the crystallite size of the silicon phase can be 50 nm or less, preferably 20 nm or less, and more preferably 10 nm or less. The crystallite size of the silicon phase can, for example, be 5 nm or more. The crystallite size of the silicon phase is calculated using the Scherer formula based on the half-width of the diffraction peaks attributable to the Si (111) plane in the X-ray diffraction (XRD) pattern.

[0047] From the perspective of increasing capacity and improving cycle characteristics, the content of silicon phase in composite particles can be above 45% by mass and below 70% by mass, above 50% by mass and below 70% by mass, or above 58% by mass and below 70% by mass, relative to the overall composite particles.

[0048] The average particle size of the composite particles can be, for example, 1 μm or more and 25 μm or less, or 4 μm or more and 15 μm or less, or 6 μm or more and 8 μm or less. Good battery performance is easily obtained within these ranges. It should be noted that the average particle size of the composite particles is the particle size that accounts for 50% of the volumetric cumulative value in the particle size distribution determined by laser diffraction scattering (volume average particle size). The measuring apparatus can be, for example, the "LA-750" manufactured by Horiba Corporation.

[0049] (Covering layer)

[0050] The negative electrode active material for secondary batteries may further include a coating layer covering at least a portion of the surface of the silicon-containing particles. The coating layer is preferably a conductive layer with electrical conductivity. By coating at least a portion of the surface of the silicon-containing particles with a conductive layer, the electronic conductivity of the silicon-containing particles is improved. Furthermore, the coating layer also has the function of suppressing electrolyte intrusion into the pores (voids) of the silicon-containing particles and suppressing side reactions. From the perspective of suppressing side reactions and maintaining higher cycle characteristics, the carbon material content is preferably 3% by mass or more and 5% by mass or less relative to the total silicon-containing particles including the coating layer.

[0051] The coating layer may contain, for example, a conductive carbon material. The coating layer is preferably thin enough not to substantially affect the average particle size of the composite particles. From the viewpoint of ensuring conductivity, the coating layer thickness is preferably 1 nm or more.

[0052] The coating or conductive layer is formed by carbonizing the carbon material raw material by mixing it with composite particles and then firing the mixture. Examples of carbon material raw materials include coal tar pitch or coal tar pitch, petroleum pitch, and phenolic resin. The firing of the mixture of carbon material raw material and composite particles is carried out, for example, in an inactive atmosphere (e.g., argon, nitrogen, etc.). The firing temperature is preferably 450°C or higher and 1000°C or lower. Within this temperature range, a highly conductive layer is easily formed in a silicate phase with low crystallinity. The firing temperature is preferably 550°C or higher and 900°C or lower, more preferably 650°C or higher and 850°C or lower. The firing time is, for example, 1 hour or higher and 10 hours or lower.

[0053] (Method for manufacturing silicon particles)

[0054] The following is a detailed description of an example of a method for manufacturing composite particles containing a lithium silicate phase, using silicon-containing particles as an example. The composite particles are manufactured, for example, by a manufacturing method including the following steps 1 to 4.

[0055] (Step 1) A process for obtaining a compound that forms an ion-conducting phase.

[0056] (Step 2) After Step 1, the compound that forms the ion-conducting phase is composited with the raw material silicon, so that the silicon phase is dispersed in the ion-conducting phase to obtain the composite intermediate.

[0057] (Step 3) A process of heat-treating the composite intermediate to obtain a sintered body containing an ion-conducting phase and a silicon phase dispersed within the ion-conducting phase.

[0058] (Step 4) A process of pulverizing the sintered body to obtain composite particles containing an ion-conducting phase and a silicon phase dispersed within the ion-conducting phase.

[0059] <Step 1>

[0060] In the first step, a compound forming an ion-conducting phase is prepared or synthesized. When the silicate phase is designated as the ion-conducting phase, the first step includes, for example, a step 1a of mixing a Si-containing raw material and a Li-containing raw material in a predetermined ratio to obtain a raw material mixture; and a step 1b of calcining the raw material mixture to obtain a raw material silicate. The calcination in step 1b is, for example, carried out in an oxidizing atmosphere. The calcination temperature of step 1b is preferably 400°C or higher and 1200°C or lower, more preferably 800°C or higher and 1100°C or lower.

[0061] Lithium silicate is produced by melting a mixture of raw materials and thinning the molten liquid into sheets using metal rollers. Then, the thinned silicate is crystallized by heat treatment in an atmospheric atmosphere at a temperature above the glass transition temperature and below the melting point. It should be noted that the thinned silicate can also be used without crystallization. Alternatively, silicates can be produced by sintering at a temperature below the melting point without melting the mixture in a specified amount, via a solid-state reaction.

[0062] Silicon (Si) feedstock can be silicon dioxide. Li (Li) feedstock can be, for example, lithium carbonate, lithium oxide, lithium hydroxide, lithium hydride, etc. The feedstock mixture can also contain elements M other than lithium, silicon, and oxygen. Element M can be added to the feedstock mixture in the form of a compound containing element M. Unreacted Si feedstock may remain within the lithium silicate. The residual Si feedstock is dispersed within the lithium silicate in the form of fine silicon dioxide crystals.

[0063] Examples of lithium compounds include lithium carbonate, lithium oxide, lithium hydroxide, and lithium hydride. A single lithium compound can be used alone, or two or more compounds can be used in combination.

[0064] As compounds containing element M, oxides, hydroxides, hydrides, halides, carbonates, oxalates, nitrates, sulfates, etc., of element M can be used. A single compound containing element M can be used alone, or two or more compounds can be used in combination.

[0065] <Second Process>

[0066] In the second step, for example, a mixture of the compound forming the ion-conducting phase (e.g., a carbon source or raw silicate) and raw silicon is pulverized while subjected to shear force to obtain a micronized composite intermediate. Here, for example, the compound forming the ion-conducting phase and raw silicon are mixed at a predetermined mass ratio (e.g., 20:80 to 95:5 mass ratio), and micronization is performed while stirring the mixture using a pulverizing device such as a ball mill. Alternatively, an organic solvent can be added to the mixture for wet pulverization. In this case, the raw silicon is micronized to form a silicon phase. The silicon phase is dispersed within the matrix of the compound forming the ion-conducting phase.

[0067] As organic solvents, alcohols, ethers, fatty acids, alkanes, cycloalkanes, silicates, and metal alkoxides can be used. The specified amount of organic solvent can be added to the grinding container all at once during the initial grinding stage, or it can be added intermittently in multiple portions during the grinding process. The organic solvent serves to prevent the material being ground from adhering to the inner wall of the grinding container.

[0068] The raw silicon can be coarse particles with an average particle size of several μm to tens of μm. The final silicon phase is preferably controlled by the fact that the half-width of the diffraction peaks belonging to the Si (111) plane in the X-ray diffraction pattern and the crystallite size calculated by the Scherer formula is 10 nm or more.

[0069] It should be noted that the compound forming the ion-conducting phase and the raw silicon can also be micronized separately and then mixed. Alternatively, silicon nanoparticles and silicate nanoparticles can be synthesized without using a pulverizing device and then mixed. Known methods such as gas-phase methods (e.g., plasma methods) and liquid-phase methods (e.g., liquid-phase reduction methods) can be used to fabricate nanoparticles.

[0070] <Step 3>

[0071] In the third step, for example, the composite intermediate, after being micronized, is subjected to pressure by hot pressing or the like while being sintered to obtain a sintered body. The sintering of the composite intermediate is, for example, carried out in an inactive atmosphere (e.g., argon, nitrogen, etc.). The sintering temperature is preferably 450°C or higher and 1000°C or lower. When the sintering temperature is within the above-mentioned temperature range, it is easy to disperse the fine silicon phase within the low-crystallinity silicate phase. During sintering, lithium silicate softens and flows in a manner that fills the gaps between silicon particles. As a result, a dense, blocky sintered body with silicate phase as the sea and silicon particles as the islands can be obtained. The sintering temperature is preferably 550°C or higher and 900°C or lower, more preferably 650°C or higher and 850°C or lower. The sintering time is, for example, 1 hour or higher and 10 hours or lower.

[0072] <Step 4>

[0073] In the fourth step, the sintered body is pulverized to have the desired particle size distribution, resulting in composite particles containing a silicate phase and a silicon phase dispersed within the silicate phase. By appropriately selecting the pulverization conditions, composite particles with a specified average particle size can be obtained.

[0074] The composition of the composite particles can be determined, for example, by the following analytical method. It should be noted that, in analyzing the composite particles contained in the negative electrode of a secondary battery, the negative electrode can be analyzed after the battery has been completely discharged. The removed negative electrode is cleaned with anhydrous methyl ethyl carbonate or dimethyl carbonate to remove non-aqueous electrolyte components, and then dried. Alternatively, a cross-section polishing machine (CP) can be used to obtain the cross-section of the negative electrode composite layer.

[0075] <EDX>

[0076] Ten composite particles with a maximum diameter of 5 μm or greater were randomly selected from cross-sectional images of the backscattered electron image (SEM) of the negative electrode mixture layer. Elemental mapping analysis based on energy-dispersive X-rays (EDX) was performed on each particle. The area ratio of the target element was calculated using image analysis software. The preferred magnification was 2000–20000x. The measured area ratios of the specified elements contained in the ten particles were averaged. The content of the target element was calculated based on the obtained average value.

[0077] The following shows the preferred measurement conditions for cross-sectional SEM-EDX analysis.

[0078] <SEM-EDX Measurement Conditions>

[0079] Processing equipment: JEOL SM-09010 (Cross Section Polisher)

[0080] Processing conditions: Accelerating voltage 6kV

[0081] Current value: 140μA

[0082] Vacuum degree: 1×10 -3 ~2×10 -3 Pa

[0083] Measurement apparatus: HITACHI SU-70 electron microscope

[0084] Accelerating voltage during analysis: 10kV

[0085] Field: Free Mode

[0086] Probe current mode: Medium

[0087] Probe current range: High

[0088] Anode Ap.: 3

[0089] OBJ Ap.:2

[0090] Analysis area: 1 μm square

[0091] Analysis software: EDAX Genesis

[0092] CPS: 20500

[0093] Lsec: 50

[0094] Time constant: 3.2

[0095] <AES>

[0096] Ten composite particles with a maximum diameter of 5 μm or greater were randomly selected from the cross-sectional image of the backscattered electron image of the negative electrode composite layer. Qualitative and quantitative elemental analysis was performed on each particle using an Auger electron spectroscopy (AES) analyzer (e.g., JAMP-9510F, manufactured by NJEOL Ltd.). Measurement conditions were set, for example, an accelerating voltage of 10 kV, a beam current of 10 nA, and an analysis region of 20 μm φ. The content of the specified element in the ten particles was calculated by averaging the content of each element.

[0097] It should be noted that during the charge-discharge process, a film is formed on the surface of the composite particles through decomposition of the non-aqueous electrolyte. Furthermore, as described later, the composite particles sometimes also possess a conductive layer covering their surface. Therefore, mapping analysis based on EDX or AES is performed on a 1 μm inward from the peripheral edge of the composite particle's cross-section, ensuring that the thin film and conductive layer are not included in the measurement range. Mapping analysis also allows confirmation of the distribution of carbon material within the composite particles. Since it is difficult to distinguish these materials from the decomposition products of the non-aqueous electrolyte at the end of the cycle, measurements of samples taken before or at the beginning of the cycle are preferred.

[0098] <ICP>

[0099] The composite particle sample was completely dissolved in a heated acid solution (a mixture of hydrofluoric acid, nitric acid, and sulfuric acid), and the carbon residue in the solution was removed by filtration. Then, the filtrate was analyzed using inductively coupled plasma optical emission spectrometry (ICP) to determine the spectral intensity of each element. Next, a standard curve was constructed using commercially available standard solutions of the elements to calculate the content of each element in the composite particles.

[0100] In addition, the contents of Na, K, Al and B contained in the composite particles can be quantitatively analyzed according to JIS R3105 (1995) (Analytical Methods for Borosilicate Glass).

[0101] In silicate-containing composite particles, both silicate and silicon phases exist. These phases can be distinguished and quantified using Si-NMR. The Si content obtained by the above method is the sum of the amount of Si constituting the silicon phase and the amount of Si in the silicate phase. The amount of Si elemental contained in the composite particles is distributed between the silicate and silicon phases using the results of quantitative analysis based on Si-NMR. It should be noted that for quantification, a mixture of silicate and silicon phases containing known Si content in a specified proportion is sufficient as the standard material.

[0102] The desired Si-NMR measurement conditions are shown below.

[0103] <Si-NMR Measurement Conditions>

[0104] Measurement apparatus: Varian Corporation, solid-state nuclear magnetic resonance spectroscopy apparatus (INOVA-400)

[0105] Probe: Varian 7mm CPMAS-2

[0106] MAS: 4.2kHz

[0107] MAS speed: 4kHz

[0108] Pulse: DD (45° pulse + 1H signal input time for decoupling)

[0109] Repeat time: 1200 sec ~ 3000 sec

[0110] Observation width: 100kHz

[0111] Observation center: around -100ppm

[0112] Signal acquisition time: 0.05 sec

[0113] Total number of times: 560

[0114] Sample volume: 207.6 mg

[0115] Figure 1 This is a schematic cross-sectional view representing an example of a negative electrode active material (composite particles). It should be noted that... Figure 1 In this text, the representation of voids or pores existing within the composite particle 23 is omitted.

[0116] The negative electrode active material 20 comprises composite particles 23 (parent particles). The composite particles 23 comprise an ion-conducting phase 21 and silicon phase (silicon particles) 22 dispersed within the ion-conducting phase 21. The composite particles 23 have an island structure in which fine silicon phase 22 is dispersed in the matrix of the ion-conducting phase 21. The surface of the composite particles 23 is covered by a conductive coating layer 26.

[0117] (Secondary battery)

[0118] The secondary battery according to the embodiments of this application includes a positive electrode, a negative electrode, and an electrolyte. The negative electrode contains the aforementioned negative electrode active material for secondary batteries. Hereinafter, the negative electrode of the secondary battery will be described.

[0119] (negative electrode)

[0120] The negative electrode, for example, comprises a negative electrode additive layer containing the aforementioned negative electrode active material for secondary batteries, and a negative electrode current collector supporting the negative electrode additive layer. The negative electrode additive layer can be formed by coating a negative electrode slurry, which disperses the negative electrode additive in a dispersion medium, onto the surface of the negative electrode current collector and then drying it. The dried coating can be calendered as needed. The negative electrode additive layer can be formed on one surface or on both surfaces of the negative electrode current collector.

[0121] The negative electrode additive contains the aforementioned negative electrode active material for secondary batteries as an essential component, and may include binders, conductive agents, thickeners, etc., as optional components. The silicon phase in the composite particles can absorb and store a large number of lithium ions, thus contributing to the high capacity of the negative electrode. The content of composite particles in the negative electrode additive layer can be more than 1% by mass and less than 50% by mass relative to the total content of the negative electrode additive layer.

[0122] The negative electrode active material may further include other active material materials that electrochemically absorb and release lithium ions. As other active material materials, carbon-based active materials are preferred, for example. Composite particles expand and contract in volume during charging and discharging; therefore, if their proportion in the negative electrode active material increases, poor contact between the negative electrode active material and the negative electrode current collector is likely to occur during charging and discharging. On the other hand, by using composite particles and carbon-based active materials in combination, the negative electrode can be endowed with high capacity of the silicon phase, and excellent cycle characteristics can be achieved. The proportion of composite particles in the total of composite particles and carbon-based active materials is preferably 0.5 to 15% by mass, more preferably 1 to 5% by mass. This makes it easy to balance high capacity and improved cycle characteristics.

[0123] Examples of carbon-based active materials include graphite, easily graphitized carbon (soft carbon), and difficult-to-graphitize carbon (hard carbon). Among these, graphite is preferred due to its excellent charge-discharge stability and low irreversible capacity. Graphite refers to materials with a graphitic crystal structure, including natural graphite, artificial graphite, and graphitized mesophase carbon particles. One type of carbon-based active material can be used alone, or two or more can be used in combination.

[0124] As the negative current collector, a non-porous conductive substrate (such as metal foil) or a porous conductive substrate (such as a mesh, reticulated sheet, or perforated sheet) can be used. Examples of materials for the negative current collector include stainless steel, nickel, nickel alloys, copper, and copper alloys. The thickness of the negative current collector is not particularly limited, but from the viewpoint of balancing the strength and lightweight of the negative electrode, 1 to 50 μm is preferred, and 5 to 20 μm is more preferred.

[0125] Examples of binders include fluoropolymers, polyolefin resins, polyamide resins, polyimide resins, vinyl resins, styrene-butadiene copolymer rubber (SBR), polyacrylic acid and its derivatives. They can be used individually or in combination of two or more. Examples of conductive agents include carbon black, conductive fibers, fluorocarbons, and organic conductive materials. They can be used individually or in combination of two or more. Examples of thickeners include carboxymethyl cellulose (CMC) and polyvinyl alcohol. They can be used individually or in combination of two or more.

[0126] Examples of dispersion media include water, alcohols, ethers, N-methyl-2-pyrrolidone (NMP), or mixtures thereof.

[0127] (positive electrode)

[0128] The positive electrode, for example, comprises a positive current collector and a positive electrode additive layer supported on the surface of the positive current collector. The positive electrode additive layer can be formed by coating a positive electrode slurry in which a positive electrode additive is dispersed in a dispersion medium onto the surface of the positive current collector and allowing it to dry. The dried coating can be calendered as needed. The positive electrode additive layer can be formed on one surface or on both surfaces of the positive current collector.

[0129] The positive electrode mixture contains a positive electrode active substance as an essential component, and may contain binders, conductive agents, etc. as optional components.

[0130] Lithium transition metal composite oxides can be used as positive electrode active materials. Examples of lithium transition metal composite oxides include Li. a CoO2, Li a NiO2, Li a MnO2, Li a Co b Ni 1-b O2, Li a Co b M 1-b O c Li a Ni 1-b M b O c Li a Mn2O4, Li a Mn2-b M b O4, LiMePO4, Li2MePO4F. Here, M is at least one element selected from Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb, and B. Me contains at least one transition element (e.g., at least one element selected from Mn, Fe, Co, and Ni). Here, 0 ≤ a ≤ 1.2, 0 ≤ b ≤ 0.9, and 2.0 ≤ c ≤ 2.3. It should be noted that the value of 'a', representing the molar ratio of lithium, increases or decreases through charging and discharging.

[0131] As a binder and conductive agent, the same material as that exemplified for the negative electrode can be used. As a conductive agent, graphite such as natural graphite and artificial graphite can be used.

[0132] The shape and thickness of the positive current collector can be selected from the shape and range based on the negative current collector. Examples of materials for the positive current collector include stainless steel, aluminum, aluminum alloy, and titanium.

[0133] (electrolytes)

[0134] The electrolyte can be a liquid electrolyte (electrolyte), a gel electrolyte, or a solid electrolyte. A liquid electrolyte is, for example, an electrolyte containing a non-aqueous solvent and a salt dissolved in the non-aqueous solvent. The concentration of the salt in the electrolyte is, for example, 0.5 mol / L or more and 2 mol / L or less. The electrolyte may contain known additives.

[0135] Gel electrolytes comprise a salt and a matrix polymer, or a salt, a non-aqueous solvent, and a matrix polymer. As a matrix polymer, for example, a polymer material that gels by absorbing a non-aqueous solvent is used. Examples of polymer materials include fluoropolymers, acrylic resins, polyether resins, and polyethylene oxide.

[0136] As a solid electrolyte, materials known in all-solid-state lithium-ion secondary batteries (such as oxide-based solid electrolytes, sulfide-based solid electrolytes, halide-based solid electrolytes, etc.) are used.

[0137] For example, liquid non-aqueous electrolytes are prepared by dissolving a salt in a non-aqueous solvent. The salt is an electrolyte salt that undergoes ion dissociation in the electrolyte; for example, it may contain lithium salts. Various additives may be included in the electrolyte. Electrolytes are typically used directly as a liquid, but they can also be used in a state where flowability is restricted by gelling agents or similar methods.

[0138] As a non-aqueous solvent, cyclic carbonates, chain carbonates, cyclic carboxylic acid esters, and chain carboxylic acid esters can be used, for example. Examples of cyclic carbonates include propylene carbonate (PC), ethylene carbonate (EC), and vinylene carbonate (VC). Examples of chain carbonates include diethyl carbonate (DEC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC). Examples of cyclic carboxylic acid esters include γ-butyrolactone (GBL) and γ-valerolactone (GVL). Examples of chain carboxylic acid esters include methyl acetate, ethyl acetate, propyl acetate, methyl propionate (MP), and ethyl propionate (EP). One non-aqueous solvent can be used alone, or two or more can be used in combination.

[0139] Examples of non-aqueous solvents include cyclic ethers, chain ethers, nitriles such as acetonitrile, and amides such as dimethylformamide.

[0140] As lithium salts, lithium salts of chlorinated acids (LiClO4, LiAlCl4, LiB) can be used, for example. 10 Cl 10 Lithium salts include those containing fluorine acids (LiPF6, LiBF4, LiSbF6, LiAsF6, LiCF3SO3, LiCF3CO2, etc.), lithium salts containing fluorine imides (LiN(CF3SO2)2, LiN(CF3SO2)(C4F9SO2), LiN(C2F5SO2)2, etc.), and lithium halides (LiCl, LiBr, LiI, etc.). A single lithium salt can be used, or two or more can be used in combination.

[0141] The concentration of lithium salt in the electrolyte can be above 1 mol / L and below 2 mol / L, or above 1 mol / L and below 1.5 mol / L. By controlling the lithium salt concentration within the above range, an electrolyte with excellent ionic conductivity and moderate viscosity can be obtained. However, the lithium salt concentration is not limited to the above concentrations.

[0142] (spacer)

[0143] Typically, a spacer is preferably sandwiched between the positive and negative electrodes. The spacer has high ion permeability and possesses moderate mechanical strength and insulation. Microporous membranes, woven fabrics, non-woven fabrics, etc., can be used as spacers. Materials used for spacers include, for example, polyolefins such as polypropylene and polyethylene.

[0144] As an example of a secondary battery structure, one can exemplify a structure in which an electrode assembly and a non-aqueous electrolyte are housed within an outer casing. This electrode assembly is formed by winding positive and negative electrodes together with a spacer between them. Alternatively, other forms of electrode assemblies, such as a stacked electrode assembly where positive and negative electrodes are layered together with a spacer between them, can be used instead of the wound electrode assembly. Secondary batteries can be of any shape, such as cylindrical, square, coin-shaped, button-shaped, or laminated.

[0145] The following is for reference Figure 2 The structure of a square non-aqueous electrolyte secondary battery, which is an example of a secondary battery in this application, will be described. Figure 2 This is a schematic perspective view showing a portion of a secondary battery from one embodiment of this application removed.

[0146] The battery has a square-shaped battery casing 4, and an electrode assembly 1 and a non-aqueous electrolyte (not shown) housed within the battery casing 4. The electrode assembly 1 has a strip-shaped negative electrode, a strip-shaped positive electrode, and a spacer between them to prevent direct contact. The electrode assembly 1 is formed by winding the negative electrode, the positive electrode, and the spacer around a flat core and then unwinding the core.

[0147] One end of the negative electrode lead 3 is mounted to the negative current collector by welding or the like. The other end of the negative electrode lead 3 is electrically connected to the negative terminal 6 provided on the sealing plate 5 via a resin insulating plate (not shown). The negative terminal 6 is insulated from the sealing plate 5 by a resin gasket 7. One end of the positive electrode lead 2 is mounted to the positive current collector by welding or the like. The other end of the positive electrode lead 2 is connected to the back of the sealing plate 5 via an insulating plate. That is, the positive electrode lead 2 is electrically connected to the battery casing 4, which also serves as the positive terminal. The insulating plate isolates the electrode assembly 1 from the sealing plate 5 and isolates the negative electrode lead 3 from the battery casing 4. The periphery of the sealing plate 5 is fitted into the opening end of the battery casing 4, and the fitting part is laser welded. In this way, the opening of the battery casing 4 is sealed by the sealing plate 5. The injection hole for the non-aqueous electrolyte provided on the sealing plate 5 is blocked by a sealing plug 8.

[0148] (Postscript)

[0149] The following technology is disclosed through the above description of the embodiments.

[0150] (Technology 1)

[0151] A negative electrode active material for secondary batteries, comprising silicon-containing particles.

[0152] The aforementioned silicon-containing particles comprise an ion-conducting phase and a silicon phase dispersed within the aforementioned ion-conducting phase.

[0153] In the aforementioned micropore size distribution of silicon particles, the average micropore size of the volume reference within the micropore size range of 2nm to 100nm is above 50nm and below 100nm.

[0154] (Technology 2)

[0155] According to the negative electrode active material for secondary batteries described in Technology 1, the aforementioned ion-conducting phase comprises at least one selected from silicate phase and silicon oxide phase.

[0156] (Technology 3)

[0157] According to the negative electrode active material for secondary batteries described in Technology 2, the silicate phase comprises at least one selected from Li2Si2O5, Li2SiO3 and Li4SiO4.

[0158] (Technology 4)

[0159] The negative electrode active material for a secondary battery according to any one of techniques 1 to 3 further comprises a coating layer covering at least a portion of the surface of the silicon-containing particles.

[0160] The aforementioned coating contains carbon materials.

[0161] The content of the carbon material is 3% by mass or more and 5% by mass or less, relative to the total silicon-containing particles including the above-mentioned coating layer.

[0162] (Technology 5)

[0163] According to any one of the techniques 1 to 4, the negative electrode active material for a secondary battery, wherein the silicon phase accounts for 45% by mass or more and 70% by mass or less in the silicon-containing particles as a whole.

[0164] (Technology 6)

[0165] According to any one of the techniques 1 to 5, the negative electrode active material for a secondary battery has an average particle size of 6 μm or more and 8 μm or less.

[0166] (Technology 7)

[0167] A secondary battery comprising a positive electrode, a negative electrode, and an electrolyte.

[0168] The aforementioned negative electrode includes the negative electrode active material for secondary batteries as described in any one of techniques 1 to 6.

[0169] [Example]

[0170] The embodiments of this application are described in detail below, but this application is not limited to the following embodiments.

[0171] Example 1

[0172] (The creation of composite particles)

[0173] <Step 1>

[0174] Silica and Li₂CO₃ were mixed and calcined in air at 950°C for 10 hours to obtain silicates. The obtained silicates were then pulverized to an average particle size of 10 μm.

[0175] <Second Process>

[0176] Silicate was mixed with raw silicon (3N, average particle size 10 μm). The mass ratio of silicate to raw silicon in the mixture was set to 42:58.

[0177] The mixture was filled into the jar (SUS, volume: 500 mL) of a planetary ball mill (Fritsch, P-5), 24 SUS balls (20 mm in diameter) were placed in the jar and the lid was closed. The mixture was then pulverized at 200–300 rpm for 25 hours in an inactive atmosphere.

[0178] <Step 3>

[0179] Next, the powdered mixture was taken out in an inactive atmosphere and sintered under pressure using a hot press in the same inactive atmosphere to obtain a sintered body of the mixture.

[0180] <Step 4>

[0181] Next, the obtained sintered body was pulverized and passed through a 40 μm sieve to obtain composite particles with an average particle size (median particle size) of 6 μm. The main component of the silicate phase in the composite particles determined by the above method is Li2Si2O5.

[0182] Next, the composite particles and coal tar pitch were mixed at a mass ratio of 95:5, and then sintered at 800°C in an argon atmosphere to form a conductive coating covering at least a portion of the surface of the composite particles, resulting in silicon-containing particles. Through sintering, the coal tar pitch was converted into amorphous carbon.

[0183] The mass ratio of the coating layer to the total mass of silicon-containing particles containing the coating layer is calculated based on the mass difference of the composite particles before and after the coating layer is formed, and the result is 3 mass.

[0184] The composite particles were placed in a measuring cell used for specific surface area determination, and the pore size distribution was measured using the method described above. Based on the logarithmic differential pore volume distribution, and considering the pore size range of 2 nm to 100 nm, the average pore size D50 was calculated using the same method. The average pore size D50 was 55 nm.

[0185] Furthermore, based on the logarithmic differential fine pore volume distribution, the porosity P(Y) is calculated when the total pore volume is assumed to be V2, taking into account the total fine pore volume V2 within the range of fine pore diameter above a specified value Y and below 100 nm. The porosity P is then expressed as a function of the fine pore diameter Y. The fine pore diameter Y when the porosity P is 50% is then calculated. P Fine aperture Y P It is 50nm.

[0186] (Making the negative electrode)

[0187] Composite particles and graphite were mixed at a mass ratio of 5:95 to serve as the negative electrode active material. Water was added to a negative electrode mixture containing the negative electrode active material, Na salt of CMC, and SBR at a mass ratio of 97.5:1:1.5, and the mixture was stirred to prepare a negative electrode slurry. Next, the slurry was applied to the surface of a copper foil at a rate of 1 m² / g. 2 The negative electrode mixture was coated with a negative electrode slurry in a manner that yielded 190g of negative electrode agent. After the coating was dried, it was calendered to produce a coating with a density of 1.5g / cm³ on both sides of the copper foil. 3 The negative electrode of the negative electrode compound layer.

[0188] (The production of the positive electrode)

[0189] NMP was added to a cathode mixture containing lithium cobalt oxide, acetylene black, and PVDF in a mass ratio of 95:2.5:2.5 and stirred to prepare a cathode slurry. Next, the cathode slurry was coated onto the surface of aluminum foil, and after drying, the coating was calendered to produce a cathode with a density of 3.6 g / cm³ on both sides of the aluminum foil. 3 The positive electrode of the positive electrode compound layer.

[0190] (Preparation of non-aqueous electrolytes)

[0191] A non-aqueous electrolyte was prepared by dissolving LiPF6 at a concentration of 1.0 mol / L in a mixed solvent containing EC and DEC in a volume ratio of 3:7.

[0192] (Making of a secondary battery)

[0193] A positive and negative electrode assembly with lead connectors installed separately was wound together with a spacer to create an electrode assembly with the lead connectors located at the outermost periphery. The electrode assembly was inserted into an outer casing made of aluminum laminate film, vacuum dried at 105°C for 2 hours, injected with a non-aqueous electrolyte, and the opening of the outer casing was sealed to obtain battery A1 of Example 1.

[0194] Examples 2-7, Comparative Examples 1-5

[0195] In the production of composite particles, by changing the pulverization conditions in the second step, the firing conditions in the third step, the mixing ratio of silicate to raw silicon, and / or the mass ratio of the coating layer to the silicon-containing particles as a whole, composite particles with an average fine pore size D50 different from those in Example 1 were obtained.

[0196] In Examples 2 and 3, the pulverization time in the second step of the composite particle production process was changed to 20 hours and 17 hours, respectively.

[0197] In Example 4, during the fabrication of the composite particles, the mass ratio of silicate to raw silicon in the mixture of silicate and raw silicon was changed to 40:60.

[0198] In Example 5, the mixing ratio of the composite particles to coal tar pitch during the fabrication of the composite particles was changed. The coating was formed with a mass ratio of 4% by mass relative to the total mass of the silicon-containing particles containing the coating.

[0199] In Example 6, the mixing ratio of the composite particles to coal tar pitch during the fabrication of the composite particles was changed. The coating was formed such that the mass ratio of the coating to the total mass of the silicon-containing particles containing the coating was 5% by mass.

[0200] In Example 7, during the fabrication of the composite particles, the average particle size of the composite particles in step 4 was changed to 8 μm. Additionally, the mixing ratio of the composite particles to coal tar pitch during the formation of the conductive coating was changed. The coating was formed such that the mass percentage of the coating relative to the total mass of the silicon-containing particles containing the coating was 5% by mass.

[0201] In Comparative Examples 1-3, the average particle size of the composite particles in the fourth step of the composite particle fabrication process was changed to 5 μm. Furthermore, the mixing ratio of the composite particles to coal tar pitch during the formation of the conductive coating was changed. The coating was formed such that the mass ratio of the coating to the total mass of the silicon-containing particles containing the coating was 2% by mass.

[0202] In Comparative Example 4, during the fabrication of the composite particles, the mass ratio of silicate to raw silicon in the mixture of silicate and raw silicon was changed to 40:60. Furthermore, similar to Comparative Examples 1-3, the average particle size of the composite particles in the fourth step was changed to 5 μm, and the mixing ratio of the composite particles to coal tar pitch when forming the conductive coating was changed. The coating was formed such that the mass ratio of the coating to the total mass of the silicon-containing particles containing the coating was 2% by mass.

[0203] In Comparative Example 5, the pulverization time in step 2 of the composite particle fabrication process was changed to 30 hours. Additionally, the average particle size of the composite particles in step 4 was changed to 9 μm. Furthermore, the mixing ratio of the composite particles to coal tar pitch during the formation of the conductive coating was changed so that the coating was formed at a mass ratio of 2.5% by mass relative to the total mass of silicon-containing particles containing the coating.

[0204] In addition, the same procedure as in Example 1 was followed to prepare composite particles and to prepare negative electrodes and secondary batteries in which the composite particles were used in active materials, resulting in batteries A2-A7 and B1-B5 of Examples 2-7 and Comparative Examples 1-5, respectively.

[0205] (evaluate)

[0206] For each battery, constant current charging is performed at 1It (800mA) until the voltage becomes 4.2V, and then constant voltage charging is performed at 4.2V until the current becomes 1 / 20It (40mA).

[0207] The negative electrode is removed from the charged battery. After cleaning the negative electrode with an organic solvent and drying it, the thickness of the negative electrode is measured at 10 randomly selected locations using a constant-pressure thickness measuring device. The average thickness is taken as the thickness T1 of the negative electrode after charge-discharge. The percentage of the thickness T1 of the negative electrode after charge-discharge relative to the thickness T0 of the negative electrode immediately after fabrication before constituting the secondary battery is evaluated as the negative electrode expansion rate. The negative electrode expansion rate is expressed by the following formula.

[0208] Negative electrode expansion rate = (T1 / T0) × 100

[0209] The evaluation results are shown in Table 1. Table 1 also shows information on the composite particles used in the negative electrode active material of each battery, including the silicon phase ratio, porosity P, and pore size Y when the porosity is 50%. P Average pore size D50, coating percentage (mass%), and average particle size.

[0210] [Table 1]

[0211]

[0212] As shown in Table 1, in batteries A1 to A7 where composite particles with an average pore size D50 of 50 nm or more and 100 nm or less are used as the negative electrode active material, the expansion of the composite particles during charging and discharging is suppressed, and the expansion of the negative electrode is also suppressed.

[0213] Preferred embodiments of the present invention have been described, but such disclosure should not be interpreted restrictively. Various modifications and alterations will undoubtedly be apparent to those skilled in the art upon reading the above disclosure. Therefore, the appended technical solutions should be interpreted as encompassing all modifications and alterations without departing from the true spirit and scope of the invention.

[0214] Industrial availability

[0215] The secondary battery of this application is useful in the main power supply of mobile communication devices, portable electronic devices, etc.

[0216] Explanation of reference numerals in the attached figures

[0217] 1: Electrode assembly, 2: Positive electrode lead, 3: Negative electrode lead, 4: Battery casing, 5: Sealing plate, 6: Negative terminal, 7: Gasket, 8: Sealing plug, 20: Negative electrode active material, 21: Ion-conducting phase, 22: Silicon phase, 23: Composite particles, 26: Coating layer.

Claims

1. A negative electrode active material for secondary batteries, comprising silicon-containing particles, The silicon-containing particles comprise an ion-conducting phase and a silicon phase dispersed within the ion-conducting phase. In the micropore size distribution of the silicon-containing particles, the average micropore size of the volume reference in the micropore size range of 2 nm to 100 nm is 50 nm or more and 100 nm or less.

2. The negative electrode active material for secondary batteries according to claim 1, wherein, The ion-conducting phase comprises at least one selected from silicate phase and silicon oxide phase.

3. The negative electrode active material for secondary batteries according to claim 2, wherein, The silicate phase comprises at least one selected from Li2Si2O5, Li2SiO3 and Li4SiO4.

4. The negative electrode active material for secondary batteries according to any one of claims 1 to 3, further comprising a coating layer covering at least a portion of the surface of the silicon-containing particles. The coating layer contains carbon material. The carbon material content is 3% by mass or more and 5% by mass or less, relative to the total silicon-containing particles including the coating layer.

5. The negative electrode active material for a secondary battery according to any one of claims 1 to 3, wherein, The silicon phase accounts for 45% to 70% by mass or more in the silicon-containing particles relative to the total silicon-containing particles.

6. The negative electrode active material for a secondary battery according to any one of claims 1 to 3, wherein, The average particle size of the silicon-containing particles is greater than 6 μm and less than 8 μm.

7. A secondary battery comprising a positive electrode, a negative electrode, and an electrolyte. The negative electrode comprises the negative electrode active material for secondary batteries as described in any one of claims 1 to 3.

Citation Information

Patent Citations

  • Secondary battery and electrolyte solution

    WO2020110917A1